2021
DOI: 10.3390/jcm10143019
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour and Anxiety Management of Paediatric Dental Patients through Virtual Reality: A Randomised Clinical Trial

Abstract: Clinicians should appreciate the effectiveness of virtual reality (VR) headsets for managing both the anxiety and the behaviour of non-cooperative paediatric patients who require treatment over several dental appointments. The aim of this study was to assess the effectiveness of using a VR headset as a distraction for managing the anxiety and behaviour of paediatric patients during their dental treatment. Eighty patients, aged between five and ten years old and who required dental treatment over three or more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 70 publications
1
19
0
Order By: Relevance
“…The results of this study corroborate reports of the effectiveness of the use of VR goggles in decreasing pain and anxiety levels during dental procedures in children aged 4 to 12 years. 9 , 16 , 17 , 18 , 19 , 24 , 25 , 26 Shetty et al 9 found statistically significant decreases in anxiety and pain levels, and also in cortisol levels before, during, and after the procedure, amongst children who used compared to those who did not use VR goggles. Ran et al 26 found that the use of VR goggles decreased levels of anxiety and pain and also shortened the duration of the procedure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of this study corroborate reports of the effectiveness of the use of VR goggles in decreasing pain and anxiety levels during dental procedures in children aged 4 to 12 years. 9 , 16 , 17 , 18 , 19 , 24 , 25 , 26 Shetty et al 9 found statistically significant decreases in anxiety and pain levels, and also in cortisol levels before, during, and after the procedure, amongst children who used compared to those who did not use VR goggles. Ran et al 26 found that the use of VR goggles decreased levels of anxiety and pain and also shortened the duration of the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…15 A number of studies have demonstrated the use of VR to reduce pain and anxiety in certain dental procedures. 9 , 16 , 17 , 18 , 19 In those randomised clinical trials, the participants were allocated to 2 groups, 1 treated with VR and the other without. Anxiety and pain were measured at the end of the dental visit, which may have varied in length, local anaesthesia method, or type of restorative treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The characteristics of all the studies included are reported in Table 2. Out of 10 incoming studies, 3 studies (30%) in Korea [2,24,25] and other studies in Brazil [19], Iran [20], Netherlands [21], Saudi Arabia [22], Republic of Korea [1], Spain [23] and China [3]. Studies in two categories of randomized trial (20%) [21,24] and randomized clinical trial (60%) [1-3, 19, 20, 22, 23, 25] Were classified.…”
Section: Characteristics Of the Studymentioning
confidence: 99%
“…Input studies included 882 participants. The mean age of participants was from 5.5 [24] to 7.9 [21,23] years.…”
Section: Characteristics Of the Studymentioning
confidence: 99%
See 1 more Smart Citation